ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN PENJULAAN PAD CAFE KOPMIL IJO PAYAKUMBUH - Supryanita, Rina; Putri, Desi Amelia (jurnal ekonomi, 2018)
This research is qualitative with the SWOT Analysis method, IFE and EFE Matrix Analysis, SWOT matrix analysis and Score Weight Analysis Table and QSPM Model. The purpose of this study was to determine and analyze marketing strategies in increasing sales at Kopmil Ijo Payakumbuh cafe. SWOT Matrix Analysis by finding four main strategies in increasing sales, namely: SO, WO, ST and WT strategies. The results showed that SO strategies had the highest score which is 3.07, followed by a WO strategy of 2.67 and an ST strategy of 2.65 and a WT strategy of 2.25. So the SO strategy that can be applied to increase sales at Cafe Kopmil Ijo Payakumbuh. Penelitian ini bersifat kualitatif dengan metode Analisis SWOT, Analisis Matriks IFE dan EFE, Analisis matrik SWOT dan Analisis Tabel Bobot Skor serta QSPM Model. Analisis Matriks SWOT dengan menemukan empat strategi utama dalam meningkatkan penjualan yaitu : Strategi SO, WO,ST dan WT.Hasil penelitian menunjukan bahwa strategi SO mempunyai skor tertinggi yaitu sebesar 3,07 ,diikuti oleh strategi WO sebesar 2,67 dan strategi ST sebesar 2,65 serta strategi WT 2,25. JadiÂ  strategi SO yang dapat diterapkan untuk meningkatkan penjualan pada Kafe Kopmil Ijo Payakumbuh